PSTha5a23, a candidate effector from the obligate biotrophic pathogen Puccinia striiformis f. sp. tritici, is involved in plant defense suppression and rust pathogenicity. (10th February 2017) - Cheng, Yulin; Wu, Kuan; Yao, Juanni; Li, Shumin; Wang, Xiaojie; Huang, Lili; Kang, Zhensheng
Summary: During the infection of host plants, pathogens can deliver virulence‐associated 'effector' proteins to promote plant susceptibility. However, little is known about effector function in the obligate biotrophic pathogen Puccinia striiformis f. sp. tritici ( Pst ) that is an important fungal pathogen in wheat production worldwide. Here, they report their findings on an in planta highly induced candidate effector from Pst, PSTha5a23. The PSTha5a23 gene is unique to Pst and shows a low level of intra‐species polymorphism. It has a functional N‐terminal signal peptide and is translocated to the host cytoplasm after infection. Overexpression of PSTha5a23 in Nicotiana benthamiana was found to suppress the programmed cell death triggered by BAX, PAMP‐INF1 and two resistance‐related mitogen‐activated protein kinases (MKK1 and NPK1). Overexpression of PSTha5a23 in wheat also suppressed pattern‐triggered immunity (PTI)‐associated callose deposition. In addition, silencing of PSTha5a23 did not change Pst virulence phenotypes; however, overexpression of PSTha5a23 significantly enhanced Pst virulence in wheat. These results indicate that the Pst candidate effector PSTha5a23 plays an important role in plant defense suppression and rust pathogenicity, and also highlight the utility of gene overexpression in plants as a tool for studying effectors from obligate biotrophic pathogens.